ESOPHAGEAL LEIOMYOSARCOMA PRESENTING WITH RECURRENT LARYNGEAL NERVE PALSY AND GREAT VESSEL ENCASEMENT: A CASE REPORT - Dr Indujaa Rajkumar, Dr Baskar A, Dr G Murugan, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Esophageal leiomyosarcoma is an extremely rare malignancy of the esophagus of esophageal tumors) and typically presents with dysphagia and weight loss in middleaged or older patients. Hoarseness of voice due to recurrent laryngeal